2019
DOI: 10.1177/0963689719860128
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell Transplantation Improves Locomotor Function in Spinal Cord Transection Rats Associated with Nerve Regeneration and IGF-1 R Expression

Abstract: Transplantation of neural stem cells (NSCs) is a potential strategy for the treatment of spinal cord transection (SCT). Here we investigated whether transplanted NSCs would improve motor function of rats with SCT and explored the underlying mechanism. First, the rats were divided into sham, SCT, and NSC groups. Rats in the SCT and NSC groups were all subjected to SCT in T10, and were administered with media and NSC transplantation into the lesion site, respectively. Immunohistochemistry was used to label Nesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…In the present study, a more significant increase in the BBB scores of rats transplanted with STAT3-RNAi- transfected NSCs was observed, with an ~50% increase in the BBB scores in that group, compared with the scores in the LC group 5 weeks following SCI. This result is superior compared with that reported by previous studies that only transplanted NSC ( 45 , 50 , 51 ). Furthermore, rats transplanted with STAT3-RNAi-transfected NSCs tended to have higher SCEP amplitudes compared with rats in the LC and SCI groups, suggesting that motor and sensory axonal conduction was reinforced following transplantation with STAT3-RNAi- transfected NSCs ( 52 ).…”
Section: Discussioncontrasting
confidence: 84%
“…In the present study, a more significant increase in the BBB scores of rats transplanted with STAT3-RNAi- transfected NSCs was observed, with an ~50% increase in the BBB scores in that group, compared with the scores in the LC group 5 weeks following SCI. This result is superior compared with that reported by previous studies that only transplanted NSC ( 45 , 50 , 51 ). Furthermore, rats transplanted with STAT3-RNAi-transfected NSCs tended to have higher SCEP amplitudes compared with rats in the LC and SCI groups, suggesting that motor and sensory axonal conduction was reinforced following transplantation with STAT3-RNAi- transfected NSCs ( 52 ).…”
Section: Discussioncontrasting
confidence: 84%
“…At molecular level, neurotrophic factors released by NSCs with the ability of promoting regeneration can help restore the function of the damaged spinal cord 49 . In addition, non-neural tissue near the site of SCI can also be repaired 50 . However, studies have found that NSCs often fail to survive and function in SCI 51 .…”
Section: Discussionmentioning
confidence: 99%
“…NSCs located in the specific regions of developing and adult human brain are tissue-specific stem cells and can terminally differentiate into all neural lineages, including neurons, astrocytes, and oligodendrocytes [ 11 ]. The application of NSCs is considered a promising therapeutic strategy for treating of central nervous system diseases, including Parkinson's disease, Alzheimer's disease, and spinal cord repair [ 12 14 ]. Preclinical researches NSCs derived from fetal tissues, ESCs, and iPSCs showed enhanced recovery after stroke [ 15 17 ] and comparable neurological disorders [ 18 , 19 ].…”
Section: Electrical Stimulation Enhances Stem Cell Neural Differentiationmentioning
confidence: 99%